DESAIN PEMBELAJARAN PAI YANG PLURALIS, INKLUSIF DAN HUMANIS: BERBASIS NILAI DAN ARAH PEMBAHARUAN - Azizah, Khoridatul; Amin, Moh. Nasrul; Nursikin, Mukh. (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
This study aims to formulate a design for Islamic Religious Education (IRE) that is pluralistic, inclusive, and humanistic—grounded in values and the direction of educational reform—in response to the challenges posed by socio-religious diversity in Indonesia. Employing a descriptive qualitative approach through a literature study, this research analyzes a wide range of academic sources and relevant IRE teaching practices. The main findings reveal that a responsive IRE instructional design that acknowledges interpretive pluralism, accommodates learners from diverse backgrounds, and upholds human values is an urgent necessity in a multicultural era. The proposed model emphasizes the integration of three core approaches: (1) pluralistic—by presenting differences among Islamic schools of thought and facilitating interfaith dialogue; (2) inclusive—by accommodating identity diversity and special needs among students; and (3) humanistic—by reinforcing the values of rahmah (compassion), ‘adl (justice), and empathy through reflective and experiential learning. The novelty of this research lies in its formulation of an instructional design that simultaneously and integrally incorporates all three approaches, in contrast to previous studies that tend to treat them in isolation. This study contributes not only by offering a more contextual and applicable curricular framework but also by recommending pedagogical strategies that position IRE as an agent of moderation and social transformation. The model is expected to serve as a reference for developing educational policies and practices in Islamic education that are adaptive to contemporary dynamics and uphold humanitarian values.